2008
DOI: 10.1136/gut.2008.162883
|View full text |Cite
|
Sign up to set email alerts
|

Results from the first three rounds of the Scottish demonstration pilot of FOBT screening for colorectal cancer

Abstract: These results are compatible with those of previous randomised trials done in research settings, demonstrating that population-based colorectal cancer screening is feasible in Scotland and should lead to a comparable reduction in disease-specific mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

21
172
5
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 158 publications
(202 citation statements)
references
References 20 publications
21
172
5
4
Order By: Relevance
“…This mirrors findings from the Scottish feasibility trials where Dropouts were also balanced by Late Entrants (Steele et al, 2009). …”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…This mirrors findings from the Scottish feasibility trials where Dropouts were also balanced by Late Entrants (Steele et al, 2009). …”
Section: Discussionsupporting
confidence: 78%
“…Reports on rates of re-participation in the literature are scarce and inconsistent, and vary depending on country and whether the data comes from randomised controlled trials, feasibility studies or full programs (Jansen, 1984;Kewenter et al, 1988;Hardcastle et al, 1996;Hart et al, 1997;Faivre et al, 1999;Mandel et al, 1999;Jorgenson et al, 2002;Weller et al, 2007;Lindholm et al, 2008;Steele et al, 2009). Some studies failed to invite firstround non-participants in subsequent rounds (Kronborg et al, 1989) although our results show that this would be unwise in organised programs because such people may become Late Entrants.…”
Section: Discussionmentioning
confidence: 65%
“…Individuals who attend screening have a 25% reduction in their risk of dying from CRC. These studies supported similar results from trials in Nottingham (Hardcastle et al, 1996;Steele et al, 2009;UK-Colorectal-Cancer-Screening-Pilot-Group, 2004). The use of flexible sigmoidoscopy has also been investigated as a screening tool (Atkin et al, 1993;UK-Flexible-Sigmoidoscopy-Screening-Trial-Investigators, 2002) which showed that a once-only flexible sigmoidoscopy between the ages of 55 and 64 could reduce CRC incidence by 33% and mortality from CRC by 43% .…”
Section: Why Screen For Bowel Cancer?supporting
confidence: 78%
“…1 Three demonstration pilot screening rounds, inviting all 50-69-year-olds, and using gFOBT alone, were carried out in 2000 -2, 2002-4 and 2005 -7 in three NHS Boards in Scotland, namely Fife, Grampian and Tayside. 2 The experience gained from the demonstration rounds informed the development of the Scottish Bowel Screening Programme (SBoSP). Roll-out of the SBoSP began in June 2007 and is now complete.…”
mentioning
confidence: 99%